Implementation of Motion Vector Steganography Method in Video - Erich Ricardo; Lolo Ate Tumangger; Diki Sahmalem Perangin Angin (Sean Institute, 2025)
The rapid development of information and communication technology has led to an increase in the exchange of digital data, particularly in the form of multimedia such as video. This condition creates a need for data security systems capable of maintaining the confidentiality of information from unauthorized parties. Steganography is one of the information security techniques that aims to hide secret messages within digital media without causing noticeable changes to the media. This study aims to implement the Motion Vector Steganography method on video media as an effective and secure technique for hiding secret messages. This method utilizes motion vectors generated during the video compression process, particularly in P-frames and B-frames, as the medium for message embedding. The research stages include analyzing video structure, embedding secret messages into motion vectors, and extracting messages from the stego video. The evaluation is conducted by comparing video quality before and after the embedding process using Peak Signal-to-Noise Ratio (PSNR) and Structural Similarity Index (SSIM) parameters, as well as testing the success of message extraction. The results show that the Motion Vector Steganography method is capable of hiding messages effectively without causing significant degradation in video visual quality. In addition, the embedded secret messages can be successfully extracted with a high level of accuracy. Therefore, this method can serve as an effective alternative solution for securing information in digital video media.